Effect of Deep Slow Breathing on Pain-Related Variables in Osteoarthritis - Kalee L. Larsen; Lorrie R. Brilla; Wren L. McLaughlin; Ying Li (Pain Research and Management)
This study evaluated the effect of a six-week deep slow breathing (DSB) program on pain, physical function, and heart rate variability (HRV) in subjects with lower extremity joint pain. Twenty subjects were assigned into training (n = 10) and control (n = 10) groups. The training group participated in a six-week DSB program consisting of weekly training sessions and at-home breathing exercises. DSB exercises focused on prolonging the exhalation and the pause following exhalation. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to assess pain and physical function, and HRV data were obtained before and after intervention. Results revealed no significant interactions between group and time for any of the variables. There was no significant main effect for group, but there was a significant main effect (p<0.025) and a large effect size for time on both pain (ηp2 = 0.454) and physical function (ηp2 = 0.506). There were no significant main effects (p>0.017) for group and time on LF power (group ηp2 = 0.039, time ηp2 = 0.061), HF power (group ηp2 = 0.039, time ηp2 = 0.039), and LF/HF ratio (group ηp2 = 0.036, time ηp2 = 0.169). Results indicated that the six-week DSB program was not sufficient to alleviate pain or improve physical function in subjects with lower extremity joint pain. Although the pain was not alleviated, other beneficial effects such as better coping with the pain were reported in the majority of training subjects. As this is the first study to examine the use of DSB for lower extremity joint pain and dysfunction, further research is needed to investigate the efficacy and applicability of DSB.